Manejo não farmacológico da dor em unidade de terapia intensiva neonatal : considerações sobre a prática assistencial do enfemeiro - Uema, Roberta Tognollo Borotta (2015)
Hospitalization during the neonatal period is increasingly common nowadays. The birth of premature babies contributes towards long hospitalization periods with consequent increase in stress situations and painful procedures. When not executed properly and with minimal care, their consequences will reverberate significantly in the future development of the baby. Analyzing the importance of care and the presence of professional nurses, the nursing team leaders, and due to their closeness to the hospitalized newborn, current research deals with the following questions: How do nurses define pain? How is pain managed in day-to-day care? What factors contribute towards the success of strategies in the relief of pain? So that professional doubts may be solved, current research demonstrates nurses´ ideas on pain in neonatology, describes the main strategies to assess, control and prevent pain, and brings forth strengths and weaknesses within the care context for the implementation of protocols for pain management. Current investigation probes into healthcare practice of nurses in pain management in neonatal intensive care units (NICU). The descriptive, exploratory, qualitative approach comprised interviews with 12 nurses working in two different neonatal units, in two municipalities in the northwestern region of the state of Paraná, Brazil. Supplementation of qualitative data included a 45-day non-participating observation period of the two units, included all shifts, during the greatest interventionist activity period. Coupled to normal procedures, a pain scale was applied during painful interventions to quantify the pain scores for classification in minimal, moderate and severe pain. Analysis of reports was based on Bardin´s thematic analysis contents. Participants were coded with letter E (interview), followed by the Arabic numeral of the sequence in which they were held. Numerical data were given in absolute and relative frequency. Research was approved by the Standing Committee in Ethics on Human Research (COPEP-UEM) of the State University of Maringa (Protocol 919,268). The assessment of results foregrounded two manuscripts: "Management of pain in neonatal intensive care unit: how are we doing?" and "Procedures in a neonatal intensive care unit: Guidelines for care improvement." The first article showed the following thematic categories: Pain assessment process; Pain record: where and how it is done; Relief strategies for pain experienced by RB; Consequences of pain in the development of the baby admitted to the NICU. The second manuscript, featuring a descriptive and observational report, registers the monitoring of 118 painful procedures, with only 34 comprising any relief interventions. Results show that the gap between theory and practice still persists and affects negatively the care provided. Decrease in the amount of procedures that the hospitalized newborn babies receive is difficult due to the great number premature infants who occupy the NICUs. Implementation strategies for pain management bundles should be undertaken, emphasizing non-pharmacological measures which are also scientifically effective in pain relief.